2012
DOI: 10.1128/jvi.06703-11
|View full text |Cite
|
Sign up to set email alerts
|

The Myristate Moiety and Amino Terminus of Vaccinia Virus L1 Constitute a Bipartite Functional Region Needed for Entry

Abstract: Vaccinia virus (VACV) L1 is a myristoylated envelope protein which is required for cell entry and the fusion of infected cells. L1 associates with members of the entry-fusion complex (EFC), but its specific role in entry has not been delineated. We recently demonstrated (Foo CH, et al., Virology 385:368 -382, 2009) that soluble L1 binds to cells and blocks entry, suggesting that L1 serves as the receptor-binding protein for entry. Our goal is to identify the structural domains of L1 which are essential for its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 84 publications
2
25
0
Order By: Relevance
“…We first examined fatty acylation as one of the known posttranslational modifications of vaccinia virus (see the introduction). One of the best known acylations in vaccinia virus is the N-terminal myristoylation of L1 protein (7,8,36). In the current study, a myristoylation mark was found at the N-terminal Gly of the initiator methionine-demethionylated Nterminal tryptic peptide of vaccinia virus protein L1R (sucrose preparation) and nowhere else in this proteome.…”
Section: Fig 2 Confidently Identified Vaccinia Virus and Host Proteinmentioning
confidence: 99%
“…We first examined fatty acylation as one of the known posttranslational modifications of vaccinia virus (see the introduction). One of the best known acylations in vaccinia virus is the N-terminal myristoylation of L1 protein (7,8,36). In the current study, a myristoylation mark was found at the N-terminal Gly of the initiator methionine-demethionylated Nterminal tryptic peptide of vaccinia virus protein L1R (sucrose preparation) and nowhere else in this proteome.…”
Section: Fig 2 Confidently Identified Vaccinia Virus and Host Proteinmentioning
confidence: 99%
“…Greater distances between α-carbons up to 3.84 Å RMSD were only found in loops. Phe108, located at the end of the cavity in L1 and required for structural integrity 33 , is conserved in all L1 orthologs except SGPV097.…”
Section: Resultsmentioning
confidence: 99%
“…A hydrophobic cavity capable of accepting and shielding a conjugated myristic acid is located near the N-terminus 32 . Myristoylation of L1 is required for infectivity but not for assembly of the EFC and incorporation into viral particles 33 . The amino acid motif for adding a myristate moiety is conserved in all poxvirus orthologs of L1, except in Salmon gill poxvirus (SGPV) 21 .…”
Section: Introductionmentioning
confidence: 99%
“…There is a large hydrophobic cavity that could accommodate the N-terminal myristate moiety [47] although this has not been demonstrated. Mutations within the cavity inhibit infectivity without affecting myristoylation [72]. A “myristate switch” model in which the acyl chain is released from the cavity during entry has been proposed.…”
Section: Membrane Fusionmentioning
confidence: 99%